PERANCANGAN SISTEM MANAJEMEN KINERJA SDM BERBASIS HUMAN RESOURCES SCORECARD DI PT ASIA PENTA GARMENT - Dini Yulianti (Universitas Insan Cendekia Mandiri, 2019)
This research aims to design HR performance management system using the HR scorecard model. This model is a layout to manage HR architecture as a strategic asset and to measure HR on business performance that connects between strategy, people, and performance from four perspectives, namely financial, consumer, internal business process, and learning and growing perspectives. Design of performance management system try to ensure performance’s standards and objectives, and is made to improve future potential performance. The resulting scores can be used as evaluation material by the company in order to improve HR performance. The result of designing HR performance management system based on HR Scorecard is to maximize the profits of the shareholders by increasing the ratio between total income and HR cost (financial perspective). Improvements of the employees’ performance score is motivated by the increase of the percentage of the employees that attend training and education to the total number of employees (internal business perspective) that has connections to the percentage of the realization of man month training and education of the employees (learning and growing perspective). The result of the HR performance measurement of the company on the whole is adequate, with score of 3.531.